2022
DOI: 10.26508/lsa.202101157
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide biosynthesis links glutathione metabolism to ferroptosis sensitivity

Abstract: Nucleotide synthesis is a metabolically demanding process essential for DNA replication and other processes in the cell. Several anticancer drugs that inhibit nucleotide metabolism induce apoptosis. How inhibition of nucleotide metabolism impacts non-apoptotic cell death is less clear. Here, we report that inhibition of nucleotide metabolism by the p53 pathway is sufficient to suppress the non-apoptotic cell death process of ferroptosis. Mechanistically, stabilization of wild-type p53 and induction of the p53 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Of the top ten processes, nine have previously been associated with AD (Figure A). , This included the dysregulated metabolism of processes associated with mitochondrial dysfunction via the serine/threonine metabolism, oxidative phosphorylation, and TCA cycle. Additionally, branched amino acid metabolism, tryptophan metabolism, glycolysis, inositol phosphate metabolism, purine metabolism, and pyruvate metabolism have all been linked to aging, loss of neuroprotective function, and increased Aβ deposition. , The drug metabolism pathway that lacked association to AD had a notable overlap of enzymes involved in glutathione, purine, and pyrimidine metabolic pathways that have been implicated in AD . Furthermore, in the AD pathway, we continued to observe associations across both regions (Figure B).…”
Section: Resultsmentioning
confidence: 64%
“…Of the top ten processes, nine have previously been associated with AD (Figure A). , This included the dysregulated metabolism of processes associated with mitochondrial dysfunction via the serine/threonine metabolism, oxidative phosphorylation, and TCA cycle. Additionally, branched amino acid metabolism, tryptophan metabolism, glycolysis, inositol phosphate metabolism, purine metabolism, and pyruvate metabolism have all been linked to aging, loss of neuroprotective function, and increased Aβ deposition. , The drug metabolism pathway that lacked association to AD had a notable overlap of enzymes involved in glutathione, purine, and pyrimidine metabolic pathways that have been implicated in AD . Furthermore, in the AD pathway, we continued to observe associations across both regions (Figure B).…”
Section: Resultsmentioning
confidence: 64%
“…Our findings indicated that erastin remarkably reduced the proliferative activity of PCa cells. In addition, Fe 2+ is one of the essential factors of DNA replication, which is vital for cell survivability [38][39][40]. Consequently, we believed that erastin primarily transforms PCa cell proliferation by altering DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked ferroptosis to nucleotide metabolism through dihydroorotate dehydrogenase (DHODH) 40 and through ribonucleotide reductase (RNR) 41 . Here, we show that alterations in nucleotide metabolism account for some of the largest changes in the metabolome of cells treated with ferroptosis inducers erastin and RSL3.…”
Section: Discussionmentioning
confidence: 99%